2011
DOI: 10.1016/j.bbr.2010.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in maternal response to immune challenge predict offspring behavior: Contribution of environmental factors

Abstract: Maternal infection during pregnancy elevates risk for schizophrenia and related disorders in offspring. Converging evidence suggests the maternal inflammatory response mediates the interaction between maternal infection, altered brain development, and behavioral outcome. The extent to which individual differences in the maternal response to immune challenge influence the development of these abnormalities is unknown. The present study investigated the impact of individual differences in maternal response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 79 publications
8
59
3
Order By: Relevance
“…Consistent with previous findings from our laboratory, polyI:C treatment reduced maternal weight in Long Evans rats (Ballendine et al 2015;Howland et al 2012;Paylor et al 2016;Sangha et al 2014;Zhang et al 2012). Others have reported that maternal weight is not consistently reduced following polyI:C administration in Sprague Dawley rats (Bronson et al 2011;Wolff and Bilkey 2010) and that weight loss was observed in Wistar rats for roughly a day, although the magnitude of loss was not quantified (Zuckerman et al 2003;Zuckerman and Weiner 2005). Maternal temperature changes in response to polyI:C administration are inconsistent in our laboratory (Ballendine et al 2015;Howland et al 2012;Sangha et al 2014;Zhang et al 2014).…”
Section: Short-term Effects Of Polyi:c Treatment On Pregnant Damssupporting
confidence: 90%
“…Consistent with previous findings from our laboratory, polyI:C treatment reduced maternal weight in Long Evans rats (Ballendine et al 2015;Howland et al 2012;Paylor et al 2016;Sangha et al 2014;Zhang et al 2012). Others have reported that maternal weight is not consistently reduced following polyI:C administration in Sprague Dawley rats (Bronson et al 2011;Wolff and Bilkey 2010) and that weight loss was observed in Wistar rats for roughly a day, although the magnitude of loss was not quantified (Zuckerman et al 2003;Zuckerman and Weiner 2005). Maternal temperature changes in response to polyI:C administration are inconsistent in our laboratory (Ballendine et al 2015;Howland et al 2012;Sangha et al 2014;Zhang et al 2014).…”
Section: Short-term Effects Of Polyi:c Treatment On Pregnant Damssupporting
confidence: 90%
“…Consideration of these data along with the PPI data suggests that this group of offspring was more mildly affected by polyI:C treatment. While the specific factors that led to this pattern of results are unclear, others have noted that body weight change in the dams following polyI:C treatment is predictive of the phenotype of the offspring (Bronson et al, 2011). Since the body weight changes observed in the dams following polyI:C treatment are of a similar initial magnitude between this data set and the other studies from our group Sangha et al, 2014;Zhang et al, 2012), other non-specific factors may have contributed.…”
Section: Effects Of Polyi:c On Behavior Of the Offspringsupporting
confidence: 56%
“…Animals were housed under standard conditions with access to food and water ad libitum . The Poly I:C treatment protocol was performed as previously described (Bronson et al, 2011; Hemmerle et al, 2015). Briefly, on gestational day 14 pregnant dams were injected with Poly I:C (8 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%